Acid Buffering Effects of Aqueous Leaf Extract of Ocimum gratissimum L. in the Rabbit Stomach - Omotoso, Dayo (My University, 2013)
Background/aims: Although the gastroprotective properties of Ocimum gratissimum L. have been mentioned, the exact mechanism is yet to be explored. Since acid output plays a significant role in the pathogenesis of gastric ulceration, the present study was aimed at investigating the effect of leaf extract of Ocimum gratissimum on gastric luminal pH, acid output, parietal cell mass and gastric mucous cell population in rabbits. Materials and Methods: The model of pyloric ligation for acid secretion and ulcer study was employed. Prior to the 4 h ligation, male New Zealand rabbits were treated orally with 75 mg/kg, 150 mg/kg and 250 mg/kg b.w aqueous leaf extract of Ocimum gratissimum twice daily for three weeks. The antisecretory and antiulcer effect of Ocimum gratissimum was compared with omeprazole (20 mg/kg p.o). Parietal cell mass and gastric mucous cell population were determined in the gastric samples by histometry. Results: Aqueous leaf extract of Ocimum gratissimum caused significant reduction in ulcer formation, gastric secretion volume and acid output in a dose dependent manner (p<0.05). Percentage inhibition was recorded as 29%, 46.2%, 52.9% for ulcer; and 16.2%, 35.9%, 52.1% for acid output upon pretreatment with 75 mg/kg, 150 mg/kg and 250 mg/kg b.w respectively. Parietal cell mass was also reduced while gastric mucous cell population and luminal pH increased accordingly when compared to the control group. Data were comparable with the antisecretory effect of omeprazole. Conclusion: The results indicate that the anti-secretory activity of Ocimum gratissimum may be the anti-ulcer mechanism of this plant.
Keywords: Ocimum gratissimum; Parietal cell mass; Mucous cell population